Complementary Eccentric Uniform Labeling Graphs - Usha, K. K.; Germina, K. A. (Journal of Informatics and Mathematical Sciences, 2016)
Given a graph \(G=(V,E)\), a set \(MV\) is called Complementary Eccentric Uniform (CEU), if the \(M\)-eccentricity labeling \(e_M(u)={d(u,v):vM}\) is identical for all \(uV-M\). The least cardinality of a CEU set is called the CEU number of the graph \(G\). In this paper we initiate a study on CEU labelled graphs and obtain bounds for certain graphs.